Constructing magnetic covalent organic framework EB-COF@Fe3O4 for sensitive determination of five benzoylurea insecticides. (15th July 2022) - Li, Shuofeng; Liu, Weihua; Wang, Qianqian; Xu, Mingming; An, Yangjuan; Hao, Lin; Wang, Chun; Wu, Qiuhua; Wang, Zhi
Highlights: A new magnetic covalent organic framework (COF) was constructed. The prepared magnetic COF exhibited excellent affinity to benzoylurea insecticides. A sensitive method was developed for detection of five benzoylurea insecticides. The magnetic COF could be used for selective extraction of benzoylurea insecticides. Abstract: A magnetic covalent organic framework (COF) was constructed with ethidium bromide (EB) and 1, 3, 5-triformylphloroglucinol as building blocks. The prepared magnetic COF (named as EB-COF@Fe3 O4 ) exhibited high adsorption ability for five benzoylurea insecticides (BUs). By combining EB-COF@Fe3 O4 based magnetic solid-phase extraction with high performance liquid-phase chromatographic detection, a novel method was developed for determination of five BUs in water and food samples. Under the optimized conditions, a good linearity was obtained to be 0.03–100.0 ng mL −1 for water and juice, 0.9–500 ng g −1 for tomato. The detection limits of the method were 0.01–0.09 ng mL −1, 0.03–0.3 ng mL −1 and 0.3–2.0 ng g −1 for water, juice and tomato samples, respectively. Satisfactory method recoveries were achieved in the range of 80.0%-116.0% with the intra-day and inter-day relative standard deviations below 10%. Moreover, the EB-COF@Fe3 O4 can be reused at least 25 times. Therefore, the established method is sensitive and robust for determining BUs in real samples.